Observing Effort Factors in the Test Design & Implementation Process of Web Services Projects - Silva-de-Souza, Thiago; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2017: Anais do II Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2017)
Several models of software testing effort estimation take into account intrinsic characteristics for the whole software development, presenting no evidence of how they effectively affect the test effort. Also, most of such estimation models only estimate the effort regarding the execution of tests. However, in software testing projects the activity usually requiring more effort is the test design & implementation one. Better precision in the identification of the effort factors influencing these activities can result in estimates with a higher degree of accuracy. Therefore, this paper presents a study on the factors affecting the effort in performing test design & implementation of large-scale software projects in a Brazilian government company. The study was carried out through observing the factors influencing the effort in two Web Services testing projects. The identified factors were made explicit through a clear description procedure, which took into account the tasks and artifacts comprising the duties regarding test design & implementation activity based on IEEE 29119 standard. It supported the identification and classification of 24 effort factors concerned with a Web Services test design & implementation process into five different categories.